The genetic contribution of HLA-DRB5*01:01 to systemic lupus erythematosus in Thailand - Louthrenoo W. (2014)
Human leucocyte antigen (HLA) study in patients with systemic lupus erythematosus (SLE) has been investigated in various countries, but the results are still inconclusive. This study was performed to investigate the association between HLA-DR and SLE in patients in northern Thailand. HLA-DR subtyping was performed in 70 patients with SLE and 99 normal healthy controls living in northern Thailand using the INNO-LiPA HLA-DR Decoder kit (Innogenetics) and MICRO SSP HLA DNA Typing kit (One Lambda) for reconfirmation. The allele frequency (AF) of DRB5*01:01 in SLE was significantly higher than in the controls [25.7% vs. 14.6%, P = 0.012, Pc = 0.048, OR = 2.02 (95%CI = 1.17-3.48)]. The AF of DRB1*15:01 and DRB1*16:02 showed a nonsignificant tendency to be higher in SLE (10.7% vs. 8.1%, and 17.9% vs. 11.1%). Interestingly, the DRB5*01:01 allele linked to DRB1*16:02 in 47.2% of SLE and 37.9% of controls, and the prevalence of the DRB1*16:02-DRB5*01:01 haplotype was higher in the patients with SLE [12.1% vs. 5.6%, P = 0.044, OR = 2.35 (95%CI = 1.06-5.19)]. The DRB1*16:02 linked to DRB5*02:02 and *02:03 in 18.2% and 31.8% of controls, respectively, and linked to DRB5*02:03 in 32.0% of SLE patients. The frequency of DRB1*03:01 and *15:02 alleles was not increased in Thai SLE. There was no significant association between DRB5*01:01 and any auto-antibodies or clinical manifestations of SLE. DRB5*01:01 is associated with Thai SLE, and the association is stronger than that of DRB1*15:01. The genetic contribution of DRB5*01:01 is due partially to the linkage disequilibrium between DRB1*16:02 and DRB5*01:01 in the northern Thai population. © 2012 Blackwell Publishing Ltd.